Evaluation of Five Alternative CO2 Capture Technologies with Insights to Inform Further Development. (July 2017) - Forsyth, Jonathan; Lodge, Stuart; Consonni, Stefano; Di Bona, Daniele; Gatti, Manuele; Martelli, Emanuele; Scaccabarozzi, Roberto; Viganò, Federico
Abstract: The high cost of CO2 capture using amine solvents from combustion sources such as natural gas-fired power plants remains a barrier to the adoption of CO2 Capture and Storage (CCS) as a climate change mitigation measure. The objective of the work reported in this paper was to carry out a preliminary assessment of the potential of five alternative technologies suitable for post-combustion CO2 capture from natural gas derived exhaust gases: CO2 permeable membranes Molten Carbonate Fuel Cells High-pressure solvent absorption from high-pressure exhaust gas from pressurised combustion / power generation High-pressure solvent absorption supported by exhaust gas compression Supersonic flow driven CO2 deposition The results of the performance and cost evaluation for each technology are explained and the prospects for significant cost reduction compared to a state-of-the-art CO2 capture process are discussed. Recommendations for further technology development activity are summarised in the conclusion of the paper.